Thousands of high-quality sequencing samples fail to show meaningful correlation between 5S and 45S ribosomal DNA arrays in humans - Ashley N. Hall (Nature Portfolio, 2021)
Abstract The ribosomal RNA genes (rDNA) are tandemly arrayed in most eukaryotes and exhibit vast copy number variation. There is growing interest in integrating this variation into genotype–phenotype associations. Here, we explored a possible association of rDNA copy number variation with autism spectrum disorder and found no difference between probands and unaffected siblings. Because short-read sequencing estimates of rDNA copy number are error prone, we sought to validate our 45S estimates. Previous studies reported tightly correlated, concerted copy number variation between the 45S and 5S arrays, which should enable the validation of 45S copy number estimates with pulsed-field gel-verified 5S copy numbers. Here, we show that the previously reported strong concerted copy number variation may be an artifact of variable data quality in the earlier published 1000 Genomes Project sequences. We failed to detect a meaningful correlation between 45S and 5S copy numbers in thousands of samples from the high-coverage Simons Simplex Collection dataset as well as in the recent high-coverage 1000 Genomes Project sequences. Our findings illustrate the challenge of genotyping repetitive DNA regions accurately and call into question the accuracy of recently published studies of rDNA copy number variation in cancer that relied on diverse publicly available resources for sequence data.